Structural materials modification during plasmochemical synthesis enriched with nanoparticles - Bolshakov, V.I.; Kalinin, A.V.; Hlushkova, D.B.; Voronkov, A.I.; Nikitchenko, I.N. (Вопросы атомной науки и техники, 2018)
The chemical composition of nanodispersed compositions was determined: SiC, TiC, TiN, Ti(CN), AlN, Mg₂Si, Mg₃N₂. The chemical composition of the synthesized compounds corresponded to the stoichiometric composition. An analysis of particles microdiffraction patterns was carried out, it was shown that nanopowders belongs to solid crystalline bodies with a metallic bond. It has been established that Ti(CN) titanium carbonitride particles are facecentered, and silicon carbide (SiC) have a hexagonal crystal lattice. Experiments on the surface modification of steels with nanopowder compositions based on Ti(CN) and SiC have been carried out. The effectiveness of using nanodispersed compositions in the smelting of structural steels has been established. As a result of the 09G2S steel modification with Ti(CN) nanopowder, the strength, plastic properties and toughness were increased. The choosing of nanodispersed Ti(CN) carbonitride powders with a fraction less than 100 nm as modifiers of low-alloy steels was substantiated. The necessary criteria for the selection of nanopowder modifiers were obtained: insolubility in melt, conformity of the crystal lattices with the matrix of steel, proportionality with the critical radius of the austenite nucleus during crystallization. The mechanism of a steel melt interaction with a layer of a nanodisperse composition was determined.